Class-AB CMOS output stages suitable for low-voltage amplifiers in nanometer technologies. (October 2019) - Giustolisi, Gianluca; Palumbo, Gaetano; Pennisi, Salvatore
Abstract: Inverting and noninverting class-AB output stages suitable for low-voltage nanometer CMOS technologies are presented, analyzed in detail and main design criteria highlighted. The solutions are based on a previous topology that is now modified and improved by avoiding both the use of floating voltage sources and the need for extensive accurate matching. As an example of application, the proposed inverting output stage is exploited in a three-stage amplifier designed in a standard 65-nm CMOS process and supplied from 1 V. Simulations show that the solution provides very good output current drive capability and current efficiency, as it is capable to source/sink a maximum output current of 1.5 mA from a quiescent value of 20 μA. Besides, it allows easy frequency compensation with very good settling performance and linearity.